2018
DOI: 10.3389/fphar.2018.00366
|View full text |Cite
|
Sign up to set email alerts
|

Targeting DNA Methyltranferases in Urological Tumors

Abstract: Urological cancers are a heterogeneous group of malignancies accounting for a considerable proportion of cancer-related morbidity and mortality worldwide. Aberrant epigenetic traits, especially altered DNA methylation patterns constitute a hallmark of these tumors. Nonetheless, these alterations are reversible, and several efforts have been carried out to design and test several epigenetic compounds that might reprogram tumor cell phenotype back to a normal state. Indeed, several DNMT inhibitors are currently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 298 publications
(344 reference statements)
0
42
0
Order By: Relevance
“…Despite positive responses in acute myeloid leukemia patients, acquired resistance is common, and these drugs are less effective in solid tumors. Improved versions are being developed and are in clinical trials for PCa (reviewed in [ 35 ] [ 36 ]), but this class of inhibitors will always have a global impact on the epigenome and therefore lack specificity for tumor suppressor genes. Thus, alternative methods targeting specific epigenetic alterations in cancer may be a more effective approach.…”
Section: Introductionmentioning
confidence: 99%
“…Despite positive responses in acute myeloid leukemia patients, acquired resistance is common, and these drugs are less effective in solid tumors. Improved versions are being developed and are in clinical trials for PCa (reviewed in [ 35 ] [ 36 ]), but this class of inhibitors will always have a global impact on the epigenome and therefore lack specificity for tumor suppressor genes. Thus, alternative methods targeting specific epigenetic alterations in cancer may be a more effective approach.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, 5-azacytidine (or azacytidine (5-aza, Vidaza ® )) and 5-aza-2′-deoxycytidine (or decitabine (DAC, Dacogen ® )) are two DNMT inhibitors approved by the European Medicines Agency (EMA) and Food and Drug Administration (FDA) for the treatment of acute myeloid leukemia (AML), myelodysplastic syndrome, and chronic myelomonocytic leukemia (CMML) [ 30 , 57 , 58 ]. DNMT inhibitors can be classified, depending on their mechanism of action, as nucleoside and non-nucleoside analogues [ 24 ].…”
Section: Dnmt Inhibitorsmentioning
confidence: 99%
“…Specifically, a high mutation rate was found in KMT2D (also known as MLL2 ) gene and in KDM6A (also referred as UTX ), which encode a histone H3 lysine 4 methyltransferase and a histone lysine demethylase, respectively [ 21 , 22 , 23 ]. The most explored epigenetic mechanism is DNA methylation [ 18 , 24 ]. By comparing methylation patterns, Wolff et al found global hypomethylation in NMIBC, whereas hypermethylation patters were more commonly found in invasive tumors, supporting the concept that DNA methylation has an important role in BC development and aggressiveness, constituting a putative target for anti-cancer therapy [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of the DNA methylation status of different TGCT types, seminoma cases have very low DNA methylation levels, whereas nonseminomatous teratomas, yolk sac tumors, and choriocarcinomas show hypermethylation due to overexpression of DNA methyltransferases (DNMT) (4). In studies to clarify epigenetic mechanisms in TGCTs, promoter methylation was shown in genes such as tumor suppressors APC, ARF, TP53, RARB2, BRCA1, RASSF1A, cell cycle regulator CCNA1, DNA repair genes such as MGMT and hMLH1, transcription factor HOXA9, and PRSS21, which encodes the protein testisin in testis cell maturation (30). Although TGCT is generally curable, resistance to cisplatin is observed in a considerable proportion of patients.…”
Section: Genetic and Epigenetic Anomalies In Tgct Development And Thementioning
confidence: 99%